Relationship between Working Memory and Early Adolescent Mathematics Learning Achievement - Linggi, Alexander Indrakusuma (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2023)
Working memory is an important cognitive ability in the learning process. This study aims to determine the relationship between working memory and mathematics achievement in early adolescent students. The research hypothesis is that there is a positive relationship between working memory and mathematics learning achievement in early adolescent students. Participants in this study were 41 students who were incidentally available at junior high schools in Semarang city. Data collection was carried out by measuring aspects of working memory, namely using Digit Span Backward and Sequencing using paper and pencil. Mathematics learning achievement using math midterm exam scores. Data analysis using pearson correlation. The results of the data analysis show that the hypothesis is accepted. Working memory has a positive correlation with mathematics learning achievement. It was concluded that working memory ability can predict mathematics learning achievement.ABSTRAKWorking memory/memori kerja merupakan kemampuan kognitif yang penting dalam proses belajar. Penelitian ini bertujuan untuk mengetahui hubungan antara memori kerja dengan prestasi belajar matematika siswa remaja awal. Hipotesis penelitian ini adalah memori kerja dengan prestasi belajar matematika pada siswa remaja awal. Partisipan dalam penelitian ini sebanyak 41 orang siswa yang tersedia secara insidental pada SMP di kota Semarang. Pengambilan data dilakukan dengan pengukuran aspek memori kerja yaitu menggunakan Digit Span Backward and Sequencing secara paper and pencil. Prestasi belajar matematika menggunakan nilai ujian tengah semester matematika. Analisis data menggunakan korelasi pearson. Hasil analisis data menunjukkan bahwa hipotesis diterima. Memori kerja memiliki korelasi positif dengan prestasi belajar matematika. Disimpulkan bahwa kemampuan memori kerja dapat memprediksi prestasi belajar matematika.